The Influence of Work-Life Balance and Career Development on Generation Z Employee Retention in Islamic Education Institutions - Riko Onki Putra; Afriyeni Afriyeni; Rani Iqasari (Yayasan Edukasi Cakrawala Nusantara, 2026)
The high turnover rate of Generation Z employees at Perguruan Islam Arrisalah averaging 9.97% per year constitutes a strategic challenge that necessitates empirical investigation into retention determinants. This study aims to analyze the effect of work-life balance and career development on Generation Z employee retention. A quantitative approach was employed, distributing questionnaires to 100 Generation Z employees via total sampling. Multiple linear regression analysis was conducted using IBM SPSS version 26. Results indicate that both work-life balance (β = 0.268; sig. = 0.019) and career development (β = 0.151; sig. = 0.037) exert a positive and significant effect on employee retention. Together, the two variables account for 32.7% of retention variance (R² = 0.327; F = 23.517; sig. = 0.000). The novelty of this study lies in its simultaneous integration of both variables within the context of a value-based Islamic educational institution—a setting that remains underexplored in human resource management literature. These findings underscore the urgency of adaptive work-life balance policies and structured career development pathways as Generation Z retention strategies in educational organizations.